Makna Simbol Dalam Novel The Fault In Our Starts - Yudi Bahtiar Permana Putra (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2022)
The research entitled “Makna Simbol dalam Novel The Fault In Our Stars karya John Green” tries to reveal the hidden meaning conveyed by the creator through the signs contained in his work. The sign analysis in this novel uses Tarigan's semantic approach. The purpose of this study is to describe the symbols in the novel The Fault In Our Stars. This study uses a qualitative descriptive method with research that focuses on the meaning of symbols. Data collection techniques used in this study are reading and recording techniques. The data used are primary and secondary data from the novel The Fault In Our Stars. Data analysis was carried out by reading and understanding the novel The Fault In Our Stars as a whole, making a synopsis, describing how a symbol in a moment that is very important to know what its meaning is, and making conclusions. The results of this study indicate that there are several real examples of a symbol that the author of the novel wants to convey through unexpected things that the readers of this novel may not know and realize. Among them is a moment where Augustus' character takes a bite of a cigarette he doesn't want to light or a swing that reminds Hazel's character of something in the past.